Analisis Puisi “Penerimaan” Karya Chairil Anwar Dengan Pendekatan Struktural (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Poetry is one of the literary genres that expresses feelings. Poetry is a poet's interpretation of life. The interpretation reflects the poet's view of the surrounding reality. Therefore poetry is a form of outpouring of thoughts and feelings poet to the reality of life. The reason the author analyzed the poem by Chairil Anwar entitled